Prevention of infection and assessment of fever following laparoscopic hysterectomy - Vineet V Mishra; Smit B Solanki; Nita V Mishra; Rohina Aggarwal; Athulya Shajan (New Indian Journal of OBGYN)
Background: A major side effect of hysterectomy is surgical site infection (SSI). Abdominal hysterectomy has higher infection rates than minimally invasive hysterectomy. The fact that fewer incisions are made as opposed to a significant front abdominal wall incision is reflected in the lower SSI rates. SSI following laparoscopic hysterectomy is prévalentdespite the reduced rates. We examine the pre-, intra-, and postoperative risk factors for infection in this article. Also included are the incidences of postoperative fever following laparoscopic hysterectomy and when does a feverish patient needs to be evaluated for infection. Method: Using phrases and keywords from the National Library of Medicine, Medical Subject Headings (MeSH) such as "postoperative," "surgical site," "infection," "fever," "laparoscopic," "laparoscopy," and "hysterectomy," PubMed was searched for papers exclusively in English. Conclusions: One of the best method to increase patient safety is to lower hospital acquired illnesses like SSI. The gynecologic surgeon or hospital might take focused preventive steps when they are aware of the risk factors for infection following laparoscopic hysterectomy.